Effect of 2’-nitroflavone on the expression of receptors associated with EGFR activity in breast cancer cells - Cebrón, Julieta Rocío (2021)
Flavonoids were proposed as chemopreventive and chemotherapeutic agents per se or in combination with traditional antitumoral drugs. Epidermal growth factor receptor (EGFR) is associated with tumorigenesis of several tissues and it can be involved in the molecular mechanism of action of several flavonoids. With the aim of investigating if a combinatory therapy involving 2'-nitroflavone (2'NF), a synthetic flavonoid with antitumor properties, and EGFRinhibitors would be a possible effective treatment for breast cancer, we studied if this flavone modulates the expression of EGFR or other receptors that interact or modulate EGFR activity. MDA-MB-231 and MCF-7 breast cancer cells were treated with 2´NF at different concentrations for48 h. Afterwards, the protein content of EGFR, ErbB2, ER alpha, Met and IGF-IR were assessed by immunoblotting. Besides, PARP cleavage and phosphorylation of p38 were determined in the same experimental conditions. Results showed that 2´NF produced a reduction on the content ofErbB2 and IGF-IR in MDA-MB-231 cells, while in MCF-7 cells a decrease on the expression of EGFR, ErbB2 and ER alpha was observed. Both cell lines presented an increment in p38 phosphorylation and PARP cleavage upon 2'NF treatment. In conclusion, 2'NF demonstrated to have effects on the expression of receptors associated with EGFR activity which could justify a possible combinatorytherapy involving 2'NF and EGFR inhibitors.